2022
DOI: 10.1017/s1368980022001227
|View full text |Cite
|
Sign up to set email alerts
|

Change in hyper-palatable food availability in the US food system over 30 years: 1988–2018

Abstract: Objective: To quantify the change in availability of hyper-palatable foods (HPF) in the US foods system over 30 years (1988 to 2018). Design: Three datasets considered representative of the US food system were used in analyses to represent years 1988, 2001, and 2018. A standardized definition from Fazzino et al (2019) that specifies combinations of nutrients was used to identify HPF. Differences in the prevalence of HPF were characterized by Cochran’s Q and McNemar’s tests. Generalized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Businesses could leverage the PSE and FME more effectively to market and incentivize the consumption of more minimally processed, whole plant-based foods and meals with healthy nutrient profiles. However, evaluations of private-sector commitments, policies, and practices of major US food and beverage manufacturers, retailers, and restaurants have shown limited progress to address the PSE and FME challenges, and to substantially shift their portfolios or prioritize communications that reinforce healthy portion size norms for their products [7,10].…”
Section: Business and Private-sector Initiatives To Promote Healthy P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Businesses could leverage the PSE and FME more effectively to market and incentivize the consumption of more minimally processed, whole plant-based foods and meals with healthy nutrient profiles. However, evaluations of private-sector commitments, policies, and practices of major US food and beverage manufacturers, retailers, and restaurants have shown limited progress to address the PSE and FME challenges, and to substantially shift their portfolios or prioritize communications that reinforce healthy portion size norms for their products [7,10].…”
Section: Business and Private-sector Initiatives To Promote Healthy P...mentioning
confidence: 99%
“…US children and adolescents have consumed larger portions of energy-dense, salty, and sweet snacks more frequently [8,9]. Over 30 y (1988Over 30 y ( -2018, US foods, sugary beverages, and meals have been manufactured to be "hyperpalatable," which is defined as a combination of fat, added sugars, carbohydrates, and/or sodium at thresholds that produce tastes that make it difficult for vulnerable individuals to stop consuming these products [4,10]. Over 20 y (2002Over 20 y ( -2021, major US food manufacturers and chain restaurants have not substantially reduced, standardized, and communicated healthy portion size norms for thousands of food and beverage products, and prepared meals marketed in the US marketplace [7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it appears that most fruits and vegetables served in school meals were not modified in a manner that may induce hyper-palatability, which is encouraging. Furthermore, while the prevalence of HPF served in school lunches was high (M = 47%), the prevalence was lower than the prevalence of HPF in the broader US food system (69%) [ 11 ]. It may be that the federal legislation requiring the presentence of both fruits and vegetables in all school lunches may be useful in displacing potentially HPF items, given our findings that fruits and vegetables were substantially less likely to be hyper-palatable than other meal items.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown to what degree HPF are present in school meals; however evidence from the broader US food environment is cause for concern. Using a standardized definition of HPF, we demonstrated that HPF have saturated the US food environment, comprising 69% of foods in the US food supply as of 2018 [ 11 ]. Groups of individuals who may be particularly vulnerable to the rewarding effects of HPF, such as infants, also have widespread exposure to HPF and have been found to consume >50% of daily energy from HPF [ 12 ].…”
Section: Introductionmentioning
confidence: 99%